2014
DOI: 10.2196/resprot.3051
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Supportive Intervention for Families Living With Depression: Content Analysis and Formative Evaluation

Abstract: BackgroundRelatives of people with a mental illness who live together can experience additional burdens that may require support. A Web-based tool including a psychoeducation module, a diary, and a password-protected forum was developed to support relatives of a person with depression.ObjectiveThe objective of our study was to explore participants’ use of the Web-based tool, with focus on the forum, and to assess its potential health and psychosocial benefits.MethodsTwenty-five people participated in this expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
11
1
7
Order By: Relevance
“…2014) and family relationships (McCann et al . 2011a; Stjernsward & Hansson 2014), causing further stress and strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014) and family relationships (McCann et al . 2011a; Stjernsward & Hansson 2014), causing further stress and strain.…”
Section: Introductionmentioning
confidence: 99%
“…Carers also frequently feel isolated (McGarry & Arthur 2001) and are unlikely to express their needs and difficulties to others (Digiacomo et al 2013). Caring also reduces the amount of time they have for themselves (Lundh 1999a), and affects social life adversely (Angermeyer et al 2006;Peraica et al 2014) and family relationships (McCann et al 2011a;Stjernsward & Hansson 2014), causing further stress and strain.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet is an essential platform for sharing and exchanging information on a multitude of topics [ 1 , 2 ]. There is, however, great variety in the types of information that are shared on the Internet, ranging from purely fact-oriented information exchange to sharing very personal information [ 3 - 5 ]. People with a common interest in a particular topic may come together on the Internet as online communities in order to share information [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One subject area for which the Internet is an important platform for information search and information exchange is the field of health-related issues [ 11 , 12 ]. In the exchange of health-related information in pertinent Internet forums [ 5 , 10 , 13 , 14 ] and online health communities [ 15 - 18 ], there is also a wide range in the variety of contributions, with both fact-oriented information exchange and the transfer of personal information. Health-related Internet forums make it possible for everyone to make contributions, that is, ask or answer questions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an online intervention that was developed for nonprofessional caregivers caring for people with dementia was well-received ( www.dementieonline.nl ). One study showed positive results of web-based peer support for families of patients with depression, although the researchers in that study recommended including professional feedback as well [ 15 ]. However, to date, no study has examined the effects of online interventions based on cognitive behavioral therapy (CBT) principles for caregivers of patients with depression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%